Antihypertensives and Statin Therapy for Primary Stroke Prevention: A Secondary Analysis of the HOPE-3 Trial. Issue 8 (August 2021) - Bosch, Jackie; Lonn, Eva M.; Dagenais, Gilles R.; Gao, Peggy; Lopez-Jaramillo, Patricio; Zhu, Jun; Pais, Prem; Avezum, Alvaro; Sliwa, Karen; Chazova, Irina E.; Peters, Ron J.G.; Held, Claes; et al.
Abstract : Background and Purpose: The HOPE-3 trial (Heart Outcomes Prevention Evaluation–3) found that antihypertensive therapy combined with a statin reduced first stroke among people at intermediate cardiovascular risk. We report secondary analyses of stroke outcomes by stroke subtype, predictors, treatment effects in key subgroups. Methods: Using a 2-by-2 factorial design, 12 705 participants from 21 countries with vascular risk factors but without overt cardiovascular disease were randomized to candesartan 16 mg plus hydrochlorothiazide 12.5 mg daily or placebo and to rosuvastatin 10 mg daily or placebo. The effect of the interventions on stroke subtypes was assessed. Results: Participants were 66 years old and 46% were women. Baseline blood pressure (138/82 mm Hg) was reduced by 6.0/3.0 mm Hg and LDL-C (low-density lipoprotein cholesterol; 3.3 mmol/L) was reduced by 0.90 mmol/L on active treatment. During 5.6 years of follow-up, 169 strokes occurred (117 ischemic, 29 hemorrhagic, 23 undetermined). Blood pressure lowering did not significantly reduce stroke (hazard ratio [HR], 0.80 [95% CI, 0.59–1.08]), ischemic stroke (HR, 0.80 [95% CI, 0.55–1.15]), hemorrhagic stroke (HR, 0.71 [95% CI, 0.34–1.48]), or strokes of undetermined origin (HR, 0.92 [95% CI, 0.41–2.08]). Rosuvastatin significantly reduced strokes (HR, 0.70 [95% CI, 0.52–0.95]), with reductions mainly in ischemic stroke (HR, 0.53 [95% CI, 0.37–0.78]) but did not significantly affect hemorrhagic (HR, 1.22 [95% CI, 0.59–2.54]) or strokes of undetermined origin (HR, 1.29 [95% CI, 0.57–2.95]). The combination of both interventions compared with double placebo substantially and significantly reduced strokes (HR, 0.56 [95% CI, 0.36–0.87]) and ischemic strokes (HR, 0.41 [95% CI, 0.23–0.72]). Conclusions: Among people at intermediate cardiovascular risk but without overt cardiovascular disease, rosuvastatin 10 mg daily significantly reduced first stroke. Blood pressure lowering combined with rosuvastatin reduced ischemic stroke by 59%. Both therapies are safe and generally well tolerated. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT00468923. Abstract : Supplemental Digital Content is available in the text.